Persistent muscle fiber regeneration in long term denervation. Past, present, future - Ugo Carraro; Simona Boncompagni; Valerio Gobbo; Katia Rossini; Sandra Zampieri; Simone Mosole; Barbara Ravara; Alessandra Nori; Roberto Stramare; Francesco Ambrosio; Francesco Piccione; Stefano Masiero; et al. (PAGEPress Publications, 2015)
Despite the ravages of long term denervation there is structural and ultrastructural evidence for survival of muscle fibers in mammals, with some fibers surviving at least ten months in rodents and 3-6 years in humans. Further, in rodents there is evidence that muscle fibers may regenerate even after repeated damage in the absence of the nerve, and that this potential is maintained for several months after denervation. While in animal models permanently denervated muscle sooner or later loses the ability to contract, the muscles may maintain their size and ability to function if electrically stimulated soon after denervation. Whether in mammals, humans included, this is a result of persistent de novo formation of muscle fibers is an open issue we would like to explore in this review. During the past decade, we have studied muscle biopsies from the quadriceps muscle of Spinal Cord Injury (SCI) patients suffering with Conus and Cauda Equina syndrome, a condition that fully and irreversibly disconnects skeletal muscle fibers from their damaged innervating motor neurons. We have demonstrated that human denervated muscle fibers survive years of denervation and can be rescued from severe atrophy by home-based Functional Electrical Stimulation (h-bFES). Using immunohistochemistry with both non-stimulated and the h-bFES stimulated human muscle biopsies, we have observed the persistent presence of muscle fibers which are positive to labeling by an antibody which specifically recognizes the embryonic myosin heavy chain (MHCemb). Relative to the total number of fibers present, only a small percentage of these MHCemb positive fibers are detected, suggesting that they are regenerating muscle fibers and not pre-existing myofibers re-expressing embryonic isoforms. Although embryonic isoforms of acetylcholine receptors are known to be re-expressed and to spread from the end-plate to the sarcolemma of muscle fibers in early phases of muscle denervation, we suggest that the MHCemb positive muscle fibers we observe result from the activation, proliferation and fusion of satellite cells, the myogenic precursors present under the basal lamina of the muscle fibers. Using morphological features and molecular biomarkers, we show that severely atrophic muscle fibers, with a peculiar cluster reorganization of myonuclei, are present in rodent muscle seven-months after neurectomy and in human muscles 30-months after complete Conus-Cauda Equina Syndrome and that these are structurally distinct from early myotubes. Beyond reviewing evidence from rodent and human studies, we add some ultrastructural evidence of muscle fiber regeneration in long-term denervated human muscles and discuss the options to substantially increase the regenerative potential of severely denervated human muscles not having been treated with h-bFES. Some of the mandatory procedures, are ready to be translated from animal experiments to clinical studies to meet the needs of persons with longterm irreversible muscle denervation. An European Project, the trial Rise4EU (Rise for You, a personalized treatment for recovery of function of denervated muscle in long-term stable SCI) will hopefully follow.